Untargeted Metabolomics and Inflammatory Markers Profiling in Children With Crohn's Disease and Ulcerative Colitis—A Preliminary Study. Issue 7 (17th February 2019) - Daniluk, Urszula; Daniluk, Jaroslaw; Kucharski, Rafal; Kowalczyk, Tomasz; Pietrowska, Karolina; Samczuk, Paulina; Filimoniuk, Aleksandra; Kretowski, Adam; Lebensztejn, Dariusz; Ciborowski, Michal
Abstract: Background: Metabolic profiling might be used to identify disease biomarkers. The aim of our study was to determine the usefulness of untargeted metabolomics analysis to detect differences in serum metabolites between newly diagnosed and untreated pediatric patients with Crohn' s disease (CD) or ulcerative colitis (UC) in comparison with a control group (Ctr). Moreover, we investigated the potential of profiling metabolomics and inflammatory markers to improve the noninvasive diagnosis of CD and UC in children. Methods: Metabolic fingerprinting of serum samples was estimated with liquid chromatography coupled with mass spectrometry in children with CD (n = 9; median age, 14 years), UC (n = 10; median age, 13.5 years), and controls (n = 10; median age, 12.5 years). Results: The majority of chemically annotated metabolites belonged to phospholipids and were downregulated in CD and UC compared with the Ctr. Only 1 metabolite, lactosylceramide 18:1/16:0 (LacCer 18:1/16:0), significantly discriminated CD from UC patients. Interestingly, combining LacCer 18:1/16:0 with other inflammatory markers resulted in a significant increase in the area under the curve with the highest specificity and sensitivity. Conclusions: Using serum untargeted metabolomics, we have shown that LacCer 18:1/16:0 is a very unique metabolite for CD patients.